Aptamer‐Functionalized Multidimensional Conducting‐Polymer Nanoparticles for an Ultrasensitive and Selective Field‐Effect‐Transistor Endocrine‐Disruptor Sensors. (31st July 2014) - Lee, Jun Seop; Kim, Sung Gun; Jun, Jaemoon; Shin, Dong Hoon; Jang, Jyongsik
<x xml:space="preserve">Abstract</x> An endocrine disruptor (ED) is a type of xenobiotic compound that can cause serious diseases related to the estrous cycle, as well as various types of cancer. At low ED concentrations, estrogen receptors may respond as they would under physiological conditions. In this work, aptamer‐functionalized multidimensional conducting‐polymer (3‐carboxylate polypyrrole) nanoparticles (A_M_CPPyNPs) are fabricated for use in an FET sensor to detect bisphenol A (BPA). The multidimensional system, M_CPPyNPs, is first produced by means of dual‐nozzle electrospray of pristine CPPyNPs and vapor deposition polymerization of additional conducting polymer. The M_CPPyNPs are then immobilized on an amine‐functionalized (–NH2) interdigitated‐array electrode substrate, through the formation of covalent bonds with amide groups (–CONH). The amine‐functionalized BPA‐binding aptamer is then introduced in the same way as that for M_CPPyNP immobilization. The resulting A_M_CPPyNP‐based FET sensors exhibit ultrasensitivity and selectivity towards BPA at unprecedentedly low concentrations (1 fm) and among molecules with similar structures. Additionally, due to the covalent bonding involved in the immobilization processes, a longer lifetime is expected for the FET sensor.